Control of flea beetle, Phyllotreta nemorum L. (Coleoptera: Chrysomelidae) using locally available natural resources - Subedi, Indra P; Vaidya, Kamini (Himalayan Journal of Sciences, 2006)
Aqueous extracts of six different plants (Acorus calamus, Ageratum conyzoides, Azadirachta indica, Duranta repens, Spilanthes acmella and Urtica dioca) and diluted animal urine (buffalo and cow) were tested for mortality rate of flea beetle (Phyllotreta nemorum) in the laboratory. Results were compared with the effects of commercial neem product (neem azal) on flea beetle mortality. The host plant taken for the study was radish (Rhaphanus sativus). Three concentrations of aqueous plant extracts (1kg/5 l, 1kg/10 l and 1kg/20 l of water), three concentrations of animal urine (20%, 15% and 10%) and two concentrations of neem azal (0.1% and 0.01%) were tested in three replications. Observations on the beetle mortality were made at 24 hrs and thereafter on alternate days for a week (168 hrs). All tested concentrations of S. acmella, buffalo urine and cow urine were effective in flea beetle control; A. calamus, A. indica and U. dioca were significantly better in controlling flea beetle (P<0.05), but only at the highest concentrations tested. The best treatments from in-vitro experimentation (the highest concentrations of S. acmella, buffalo urine and cow urine) were evaluated further in vivo. Results showed that all three treatments were effective in controlling the flea beetle (P<0.05).Key words: Cattle urine, marati, neem, neem azal, radishHimalayan Journal of Sciences 1(2): 111-114, 2003